Culture, re-traditionalization, and subordination - Haqmoradi, Mohammad (Sulaimani Journal for Humanities, 2025)
Culture refers to how we think about ourselves and how we formulate our problems and issues. In a critical perspective, a society's cultural approach can act like an internal or self-made ideology, portraying a false and distorted world of itself and the historical situation it finds itself in, and presenting a false narrative of itself and society. Most people participate in the production and reproduction of this discourse or cultural approach. The "Kurdayeti" discourse, in some of its dimensions, has not confronted the orientalist and centrist epistemological order, but has largely internalized it. Instead of confronting it critically, this cultural discourse has internalized it and has not rejected it. The aim of this research is to try to disrupt and subvert the cultural discourse of Kurdish society. It also proposes a critical and historical reflection on Kurdish society. It aims to study the relationship between social structure and culture and the consequences of Kurdish cultural discourse. Accordingly, it raises the question of how Kurds define themselves in their cultural activities. In this way, the researcher aims to problematize the social structure by problematizing the dominant cultural approach to the Kurds. He also explains the social and political consequences of this process, such as the re-traditionalization of Kurdish society.
Keywords: culture; retraditionalization; problematization; aestheticization; anthropological; territory